2012
DOI: 10.1088/1478-3975/9/2/026004
|View full text |Cite
|
Sign up to set email alerts
|

Single-molecule dynamics of transcription of the lar promoter

Abstract: We measured the in vivo production of RNA molecules tagged with MS2d-GFP in Escherichia coli, driven by the lar promoter, under weak and medium induction. The distributions of intervals between consecutive productions of RNAs are found to be sub-exponential, and the process of RNA production is found to be sub-Poissonian. We discuss possible models of transcription initiation and, based on our results and previous in vitro measurements, find that a sequential two-step model of transcription initiation at the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
59
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(65 citation statements)
references
References 39 publications
(98 reference statements)
6
59
0
Order By: Relevance
“…Two studies reported in vivo measurements of the kinetics of P lac/ara-1 [21,22]. In these, the RNA is visible shortly after transcription occurs by tagging them with MS2d-GFP proteins [23].…”
Section: Introductionmentioning
confidence: 99%
“…Two studies reported in vivo measurements of the kinetics of P lac/ara-1 [21,22]. In these, the RNA is visible shortly after transcription occurs by tagging them with MS2d-GFP proteins [23].…”
Section: Introductionmentioning
confidence: 99%
“…With proper parameter values, the gamma distribution well approximates recent live cell measurements of intervals between productions of consecutive RNAs in E. coli [13,20]. We fitted the measurements of time intervals in [20] with the three-exponential model proposed in that work, and with a gamma distribution. The latter results in ( α M , ( α M k M ) -1 ) of (2.27183, 1070.57) and (2.51171, 565.956) for the low and medium induction levels, respectively.…”
Section: Methodsmentioning
confidence: 91%
“…In our implementation, each time this reaction occurs, a value of τ S is drawn from a gamma distribution with mean of k M -1 and coefficient of variation (variance over the mean) of αMMathClass-bin-1MathClass-bin/2. With proper parameter values, the gamma distribution well approximates recent live cell measurements of intervals between productions of consecutive RNAs in E. coli [13,20]. We fitted the measurements of time intervals in [20] with the three-exponential model proposed in that work, and with a gamma distribution.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations